Utilization of Information and Communication Technology in the Tax Administration System to Increase Taxpayer Compliance - Intan Arsitia Djafri; Intan Damawati; Suharto Suharto; I Gusti Agung Raka Putra Satwika; Rahmatullah Rahmatullah (Yayasan Ilomata, 2023)
Adaptation to changes based on information and communication technology (ICT) causes obstacles and community preparedness for the 5.0 age, also known as society 5.0. This necessitates the digital revolution of all disciplines, including taxation. Government efforts to promote taxpayer compliance include creating a contemporary tax administration system encompassing organizational structure, business processes, information and communication technology, human resource management, and applying good governance. In addition to the tax administration system, taxpayer knowledge also influences the level of taxpayer compliance. This study's objective is to investigate the use of ICT in a modern tax administration system to enhance taxpayer compliance. The main theory in this research is positive accounting theory which was developed by Watt & Zimmerman in 1986. This study employs a qualitative approach and descriptive methodologies. This study demonstrates that the incorporation of ICT is a component of the modernization of the tax administration system. Application of the e-tax system, which comprises E-Registration, E-SPT, E-Filing, E-Payment, Blockchain, Artificial Intelligence (AI), Chatbots, and Biometric Identification, can constitute the use of ICT in the tax administration system. Ease of service, particularly in filling out SPT electronically, or e-SPT, is the method for boosting taxpayer compliance with the modernization of the tax administration system utilizing ICT.